Preemptive Immunotherapy for Minimal Residual Disease in Patients With t(8;21) Acute Myeloid Leukemia After Allogeneic Hematopoietic Stem Cell Transplantation - Fan, Shuang; Shen, Meng-Zhu; Zhang, Xiao-Hui; Xu, Lan-Ping; Wang, Yu; Yan, Chen-Hua; Chen, Huan; Chen, Yu-Hong; Han, Wei; Wang, Feng-Rong; Wang, Jing-Zhi; Zhao, Xiao-Su; et al. (Frontiers in Oncology, 2022)
In patients with t(8;21) acute myeloid leukemia (AML), recurrent minimal residual disease (MRD) measured by RUNX1-RUNX1T1 transcript levels can predict relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT). This study aimed to compare the efficacy of preemptive interferon (IFN)-α therapy and donor lymphocyte infusion (DLI) in patients with t(8;21) AML following allo-HSCT. We also evaluated the appropriate method for patients with different levels of RUNX1-RUNX1T1 transcripts. In this retrospective study, consecutive patients who had high-risk t(8;21) AML and received allo-HSCT were enrolled. The inclusion criteria were as follows: (1) age ≤65 years; (2) regained MRD positive following allo-HSCT. MRD positive was defined as the loss of a ≥4.5-log reduction and/or <4.5-log reduction in the RUNX1-RUNX1T1 transcripts, and high-level, intermediate-level, and low-level MRDs were, respectively, defined as <2.5-log, 2.5−3.5-log, and 3.5−4.5-log reductions in the transcripts compared with the pretreatment baseline level. Patients with positive RUNX1-RUNX1T1 could receive preemptive IFN-α therapy or DLI, which was primarily based on donor availability and the intentions of physicians and patients. The patients received recombinant human IFN-α-2b therapy by subcutaneous injection twice a week every 4 weeks. IFN-α therapy was scheduled for six cycles or until the RUNX1-RUNX1T1 transcripts were negative for at least two consecutive tests. The rates of MRD turning negative for patients with low-level, intermediate-level, and high-level RUNX1-RUNX1T1 receiving IFN-α were 87.5%, 58.1%, and 22.2%, respectively; meanwhile, for patients with intermediate-level and high-level RUNX1-RUNX1T1 receiving DLI, the rates were 50.0% and 14.3%, respectively. For patients with low-level and intermediate-level RUNX1-RUNX1T1, the probability of overall survival at 2 years was higher in the IFN-α group than in the DLI group (87.6% vs. 55.6%; p = 0.003). For patients with high levels of RUNX1-RUNX1T1, the probability of overall survival was comparable between the IFN-α and DLI groups (53.3% vs. 83.3%; p = 0.780). Therefore, patients with low-level and intermediate-level RUNX1-RUNX1T1 could benefit more from preemptive IFN-α therapy compared with DLI. Clinical outcomes were comparable between preemptive IFN-α therapy and DLI in patients with high-level RUNX1-RUNX1T1; however, they should be further improved.